Fear and Entrepreneurship: A Review and Research Agenda1. (April 2015) - Cacciotti, Gabriella; Hayton, James C.; Grégoire, Denis A.; Cornelissen, Joep; Dimov, Dimo; van Burg, Elco
<x xml:space="preserve">Abstract</x> A systematic review of the entrepreneurship literature on fear published up to 2014 highlights several key characteristics. First, the predominant focus in research examining the emotion of fear in entrepreneurship is on the specific concept of fear of failure. However, this literature shows a lack of precision in the conceptualization and operationalization of this construct. The impact of the experience of fear on individual cognition and behaviour can be beneficial as well as detrimental. Despite this dualistic nature, to date, fear is examined as only a barrier to entrepreneurial behaviour. This review reveals a clear dichotomy in the literature, with significantly more focus on fear as a trait that distinguishes between people than as a temporary state that is commonly experienced by many people. Defining fear of failure as a context‐specific phenomenon, this paper explains the importance of focusing on the temporary cognitive and emotional experience of fear and use conceptual observations as a platform to develop an agenda for future research.